Students' Perceptions of Part-Time Jobs And Organizational Activities Academic Performance In Students State University of Malang - Kurniawan, Novian Candra; Idris (Jurnal Pendidikan Ilmu Sosial, 2023)
Academic achievement is something that students dream of because it is considered to provide more value when entering the world of work. In addition, they, at the same time, also do other activities such as working or organizing. Thus, time management between lectures and other activities becomes a problem for students. This study aims to examine students' perceptions of the relationship between part-time jobs, organizational activities, and academic achievement. Quantitative approach with explanatory type is used in this study. Data in this study were collected through questionnaires and google form. Using multiple linear regression test, this study found that part-time job and organizational activities positively and significantly affect academic achievement. The more active students are in activities other than lectures, especially participating in organizational activities or working part-time, the higher their achievement.